Analisis Pengetahuan Ibu Nifas Dalam Melakukan Perawatan Payudara Dengan Kelancaran Produksi ASI Di PMB WW Cikarang Utara Bekasi : (Knowledge Analysis of Postpartum Mothers in Performing Breast Care with Smooth Milk Production at PMB WW Cikarang Utara Bekasi - Nuraidah, Rohmah; Novita (Dohara POAJ, 2023)
Introduction: The postpartum period is a period of recovery from nine months of pregnancy and the birth process which a mother goes through after giving birth to her child and lasts for approximately six weeks. Expulsion of breast milk or lactation is a sign of the physiological changes experienced by postpartum mothers during this period. Methods: Analytical with a cross-sectional approach. The sample in this study were postpartum mothers at PMB WW Cikarang Utara Bekasi in November 2022 as many as 32 people (total sampling). Results: There is an influence of knowledge of postpartum mothers on breast care it is proven to have an effect on the smoothness of ASI (ρ-value of 0,005 < 0,05). Discussion: The results of this study are expected to provide information about breast care on the smooth expulsion of breast milk in postpartum mothers for postpartum mothers either through midwifery care when the mother is doing prenatal checks or through health counseling.